Informe pasantía de investigación: Prospectiva de las industrias culturales y creativas, sector editorial (2022)
This report includes a contribution to the research of cultural and creative industries, where different aspects relevant to the development and origin of CHF in different populations are evidenced, specifically in the city of Bogotá. On the other hand, the behavior of the publishing sector in Colombia is analyzed, studying the occupational profiles required in this industry, highlighting the implementation of the creative economy within the development plans of each government